Two homologous sequences of Grp78 and HSP70 represent tumor antigens shared with streptococcal superantigens in eliciting an antitumor immune response: an immunoinformatic investigation - Finotti, Paola (Frontiers in Immunology, 2025)
Bacteria-based therapies have gained increasing attention as novel immunotherapeutic approaches against tumors. Among them, bacteria producing superantigen (SAg) toxins are considered particularly effective due to their ability to induce potent, generalized inflammatory responses capable of destroying tumor cells. Building on evidence of the antitumor efficacy of certain streptococcal preparations, and on the known involvement of heat shock proteins (HSPs) in tumor progression, we tested the hypothesis that streptococcal SAgs may elicit an adaptive immune response against tumors by priming cytotoxic T cells with epitopes that closely resemble tumor-associated HSPs. Through a multistep immunoinformatic analysis, we identified HSP70, Grp78, and Grp94 as containing immunogenic epitopes with high similarity to those found in the SAg domains of streptococcal exotoxins. Notably, a long sequence of HSP70 and its homolog in Grp78 was found to harbor multiple immunodominant epitopes overlapping the MHC class I and II epitopes of exotoxins, also containing B-cell epitopes. Results suggest that specific sequences of HSP70 and Grp78 may act as shared tumor antigens targeted by the immune response initiated by streptococcal SAgs, supporting their potential use as peptide-based tumor vaccines.